How to One Up a Pandemic: University of Minnesota's Physical Medicine and Rehabilitation Virtual Clerkship—A Model for Alternative Clinical Training and Preliminary Validation Study. (November 2021) - Topor, Lauren; Balser, David; Bruhnding, Paul; Dvorak, James; Anderson, Carly; Tanguay, Bethany; Seidel, Erica; Tonkin, Brionn; Senk, Alexander
Abstract : Abstract: Drastic and rapid changes to medical education are uncommon because of regulations and restrictions designed to ensure consistency among medical school curriculums and to safeguard student well-being. As a consequence of the COVID-19 pandemic, medical education had to break away from its conventions and transition from time-honored teaching methods to innovative solutions. This article explores the anticipated and actual efficacy of the swift conversion of a specialty elective from a traditional in-person format to a fully virtual clerkship. In addition, it includes a noninferiority study to determine where a virtual classroom may excel or fall short in comparison with conventional clinical rotations. Abstract : Supplemental digital content is available in the text.